Looking Forward to Better Feauture Detection - Ellis, Colin K. (The International Hydrographic Review, 2015)
This is a military surveyor’s perspective on the potential for the Three Dimensional Forward Looking Sonar (TDFLS) and reports on the Australian developments todate with this concept. The TDFLS concept as currently being developed in Australia, can enhance navigation safety and optimise specific military missions by providing systematic sonar ensonification and intuitive, high resolution data. TDFLS may also revolutionise mission efficiency and safety within the Hydrographic feature detection mission by allowing faster vessel speeds, wider line spacings and easier planning. The views expressed in this paper are those of the author but reflect Royal Australian Navy (RAN) Hydrographic Service policy on feature detection.